Approaching microwave photon sensitivity with Al Josephson junctions - Pankratov, Andrey L.; Gordeeva, Anna V.; Revin, Leonid S.; Ladeynov, Dmitry A.; Yablokov, Anton A.; Kuzmin, Leonid S. (Beilstein Journal of Nanotechnology, 2022)
Here, we experimentally test the applicability of an aluminium Josephson junction of a few micrometers size as a single photon counter in the microwave frequency range. We have measured the switching from the superconducting to the resistive state through the absorption of 10 GHz photons. The dependence of the switching probability on the signal power suggests that the switching is initiated by the simultaneous absorption of three and more photons, with a dark count time above 0.01 s.
Keywords: Josephson junction; microwave photons; single photon counter; thermal activation